The Contribution of Specific Pneumococcal Serogroups to Different Disease Manifestations: Implications for Conjugate Vaccine Formulation and Use, Part II - William P. Hausdorff; John Bryant; C. Kloek; Peter R. Paradiso; George R. Siber (2000)
To assess whether certain serogroups of Streptococcus pneumoniae are preferentially associated with specific disease manifestations, we analyzed all recent pneumococcal disease studies and assessed the relative frequency of isolation of each serogroup by clinical site (as a proxy for different disease states). In all age groups, serogroups 1 and 14 were more often isolated from blood, and serogroups 6, 10, and 23 were more often isolated from cerebrospinal fluid (CSF); in young children, serogroups 3, 19, and 23 were more often isolated from middle ear fluid (MEF). Serogroups represented in conjugate vaccines were isolated slightly less frequently from CSF than from blood or MEF. Nonetheless, serogroups in the 9-valent conjugate vaccine formulation still comprised ∼75% of pneumococcal isolates from the CSF of young children in Europe and in the United States and Canada. These analyses indicate that pneumococcal conjugate vaccines could potentially prevent a substantial proportion of episodes of bacteremic disease, pneumonia, meningitis, and otitis media, especially in young children.